The Role of Reform in Selected German-Jewish Orthodox Responsa: A Sociological Analysis - Ellenson, David Harry (Hebrew Union College annual / Jewish Institute of Religion, 1982)
This paper analyzes rabbinic legal literature (responsa) issued by three prominent German Orthodox rabbis — Esriel Hildesheimer (1820-1899), David Hoffmann (1843-1921), and Marcus Horovitz (1844-1910) — in light of Kai Erikson's approach to deviance theory in sociology. Leaning on Erikson, this study takes the position that "deviance is an integral part of every healthy society," inasmuch as the labelling of certain acts or beliefs by a group as "deviant" aids the group in clarifying its own norms and in establishing boundaries for acceptable group practice and belief. Furthermore, the group, through the process of defining unacceptable practices and beliefs as "deviant," comes to coalesce and unite in a common posture concerning the deviant behavior or view. Building upon this theoretical insight, the paper proposes that Reform Judaism played precisely this role in the process of identity formation and boundary maintenance for Orthodox Judaism in Germany during the latter part of the nineteenth century and in the early years of the twentieth. By looking at selected responsa of Hildesheimer, Hoffmann, and Horovitz, and by analyzing the role Liberal Judaism was assigned in these judgments, we identify the process of Orthodox Jewish identity formation in Germany and the contribution Reform made to this process. Through this perspective various social dynamics of the Jewish community in the modern era are considered and something of the nature of religious group establishment is clarified.